2016
DOI: 10.1111/apm.12596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two assays for CXCL13 analysis in cerebrospinal fluid for laboratory diagnosis of Lyme neuroborreliosis

Abstract: Henningsson AJ, Gyllemark P, Lager M, Skogman BH, Tjernberg I. Evaluation of two assays for CXCL13 analysis in cerebrospinal fluid for laboratory diagnosis of Lyme neuroborreliosis. APMIS 2016; 124: 985-990 We evaluated the diagnostic performance of two assays, one bead-based assay and one enzyme-linked immunosorbent assay (ELISA), for the determination of CXCL13 levels in cerebrospinal fluid (CSF) from patients with suspected Lyme neuroborreliosis (LNB). Patients investigated for LNB were retrospectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 21 publications
4
21
2
1
Order By: Relevance
“…These results are consistent with those observed in several previous studies [ 18 20 , 22 , 28 , 29 ], all supporting the hypothesis that elevated concentrations of CXCL13 in CSF can be used as a marker for LNB. However, the overall sensitivity (88%) and overall specificity (89%) observed in our study were moderate, compared to previous studies on CXCL13 in CSF with sensitivities ranging between 88 and 100% and specificities between 89 and 100% [ 18 , 19 , 22 , 25 , 29 , 30 ]. The variation in diagnostic performances between these studies may partly be explained by differences in classification of LNB patients and controls, the use of different laboratory methods with different intra-assay variability, and variations in cut-off levels for CXCL13 (ranging between 55 and 415 pg/mL) [ 18 , 19 , 25 , 29 ].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with those observed in several previous studies [ 18 20 , 22 , 28 , 29 ], all supporting the hypothesis that elevated concentrations of CXCL13 in CSF can be used as a marker for LNB. However, the overall sensitivity (88%) and overall specificity (89%) observed in our study were moderate, compared to previous studies on CXCL13 in CSF with sensitivities ranging between 88 and 100% and specificities between 89 and 100% [ 18 , 19 , 22 , 25 , 29 , 30 ]. The variation in diagnostic performances between these studies may partly be explained by differences in classification of LNB patients and controls, the use of different laboratory methods with different intra-assay variability, and variations in cut-off levels for CXCL13 (ranging between 55 and 415 pg/mL) [ 18 , 19 , 25 , 29 ].…”
Section: Discussioncontrasting
confidence: 91%
“…It has also been suggested that CXCL13 in the CSF may be a marker for disease duration [ 21 ]. Different methods and cut-off levels have been suggested in different studies [ 18 , 19 , 22 25 ], but no consensus has been established so far.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies measuring CXCL13 using ELISA and lateral flow (LFA) methods have shown elevated CXCL13 circulation levels in the CSF of patients with acute neuroborreliosis compared to other tested groups. Results of the available studies suggest its very high diagnostic value and report its high sensitivity and specificity [5][6][7][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. These studies are in agreement with a meta-analysis performed by Yang J. et al, who confirmed that CXCL13 has a high sensitivity and specificity for diagnosing neuroborreliosis [68].…”
Section: Cxcl13 Concentrationsupporting
confidence: 85%
“…It also may indicate that CXCL13 correlates better with pleocytosis than with the CSF-specific antibodies index. Such results also suggest that CXCL13 levels can be helpful in distinguishing the activity and acuteness of the current infection from previous infections [5,34,[37][38][39][40]. Levels of the chemokine in possible neuroborreliosis with negative specific antibodies has been found not to differ from other neurological conditions, e.g., multiple sclerosis, viral meningitis, neurosyphilis, or lupus [41].…”
Section: Cxcl13 Concentrationmentioning
confidence: 88%
See 1 more Smart Citation